The Microbiome in Posttraumatic Stress Disorder and Trauma-Exposed Controls: An Exploratory Study. Issue 8 (October 2017) - Hemmings, Sian M.J.; Malan-Müller, Stefanie; van den Heuvel, Leigh L.; Demmitt, Brittany A.; Stanislawski, Maggie A.; Smith, David G.; Bohr, Adam D.; Stamper, Christopher E.; Hyde, Embriette R.; Morton, James T.; Marotz, Clarisse A.; Siebler, Philip H.; et al.
ABSTRACT: Objective: Inadequate immunoregulation and elevated inflammation may be risk factors for posttraumatic stress disorder (PTSD), and microbial inputs are important determinants of immunoregulation; however, the association between the gut microbiota and PTSD is unknown. This study investigated the gut microbiome in a South African sample of PTSD-affected individuals and trauma-exposed (TE) controls to identify potential differences in microbial diversity or microbial community structure. Methods: The Clinician-Administered PTSD Scale for DSM-5 was used to diagnose PTSD according to Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition criteria. Microbial DNA was extracted from stool samples obtained from 18 individuals with PTSD and 12 TE control participants. Bacterial 16S ribosomal RNA gene V3/V4 amplicons were generated and sequenced. Microbial community structure, α-diversity, and β-diversity were analyzed; random forest analysis was used to identify associations between bacterial taxa and PTSD. Results: There were no differences between PTSD and TE control groups in α- or β-diversity measures (e.g., α-diversity: Shannon index, t = 0.386, p = .70; β-diversity, on the basis of analysis of similarities: Bray-Curtis test statistic = –0.033, p = .70); however, random forest analysis highlighted three phyla as important to distinguish PTSD status: Actinobacteria, Lentisphaerae, and Verrucomicrobia. Decreased total abundance of these taxa was associated with higher Clinician-Administered PTSD Scale scores ( r = –0.387, p = .035). Conclusions: In this exploratory study, measures of overall microbial diversity were similar among individuals with PTSD and TE controls; however, decreased total abundance of Actinobacteria, Lentisphaerae, and Verrucomicrobia was associated with PTSD status. Abstract : Supplemental digital content is available in the text.